Can Politics Tame the Market? Market Responses to Government Control of Fully and Partially Privatized Firms in China - Christos Mavrovitis (Mavis); Sarmistha Pal (Institute of Labor Economics (IZA), 2025)
This study examines factors influencing full (FP) versus partial (PP) privatization and how markets respond to government control in PP and FP firms. Exploiting China's 2005 NTS reform as a natural experiment, we find that treated PP firms experienced significantly lower post-reform performance, driven by persistent private benefits of control, failure to adopt value-maximizing behavior, and unchanged liquidity and information asymmetry. In contrast, FP firms eliminated all NTS, maximized value; showed higher stock market liquidity and lower information asymmetry, improved market performance; and gained market confidence in the post-reform period. These findings challenge the effectiveness of China's authoritarian approach to private sector development.
Keywords: G31; G38; L33; 330; local government incentives; authoritarian central government; firm value maximization; full and partial privatization; non-tradable shares reform; difference-in-differences